Contents of Korean literature that should be introduced in the Russian Federation - Youngsuk Kim, Svetlana Yurievna Glushkova, Young Cheol Ko, (Opción, 2019)
The purpose of this study is to analyze the contents of Korean literature that had been already published in Russia. The research methods used in this study were literature survey, internet data search and percentage statistics. As a result, 17% of the former ages textbooks, 62% of ancient textbooks, and 21% of modern textbooks are considered to be necessary to publish textbooks on modern Korean literature. In conclusion, the Korean literature to be introduced in Russia is the translation of the work which can have world appeal with the most Korean authentic thing in it.